Educational Leadership on the Social Frontier: Developing Promise Neighborhoods in Urban and Tribal Settings. (October 2013) - Miller, Peter; Wills, Nathan; Scanlan, Martin
We examined how the federal Promise Neighborhoods program shapes leadership networks and objectives in diverse tribal and urban settings. The program calls for diverse stakeholders to provide families with resources such as parenting workshops, childcare, preschool, health clinics, and other social services that affect learning and development. We focused particularly upon how Promise Neighborhoods planning and development creates new "frontiers of educational leadership." We analyzed Promise Neighborhoods planning grant applications—21 that were funded and 21 from tribal settings—as well as interview data and program and community-specific archival data to learn about applicants' purposes and compositions of partners. These data were analyzed with insights from Burt's notion of structural holes, which suggests that leadership in "social frontier" spaces is often dependent upon negotiation, entrepreneurship, and relationship brokering. While both urban and tribal applicants were found to have highly diverse compositions of partners, tribal partners were more heterogeneous and separated by greater geographic distances. Additionally, tribal applicants' stated purposes and goals were tied more closely to local cultures and customs. We note that the sprawling spaces and significant inter- and intracommunity differences of the tribal Promise Neighborhoods ensure that leadership practice in these settings is especially dependent upon negotiation and relationship brokering. As Promise Neighborhoods and other place-based initiatives are developed, diverse networks of leaders will be called to bridge organizational boundaries, cultural differences, socioeconomic differences, and physical distances to develop coherent plans of action for collective "Neighborhoods."